Analisis Pengaruh Dimensi Kualitas Layanan terhadap Kepuasan Konsumen dan Niat Melakukan Pembelian Kembali Layanan Laundry di Indonesia - Brigitta Estella; Kelvin Wongso; Raymond Raymond; Ricky Tjayadi (Universitas Prasetiya Mulya, 2019)
In this era, urban people are getting busier everyday and have less spare time for themselves; let alone to do household chores. Whereas, there are a lot of household chores that needs to be done everyday, such as washing clothes. Therefore, laundry is one the in demand service. As a washing service provider , the quality of the service is becoming the key excellence that is significant towards the laundry 's success. For that reason, this research is made to measure the factors from service quality theory such as tangibility, assurance, empathy, responsiveness, and reliability; with its relation with customer satisfaction that resulting in repurchase intenifi's. Findings of this research can be used to increase the quality of laundry to meet customer needs and wants accurately. The correlation between service quality (servqual) with customer satisfaction based on the questionnaire data that is analyze with SPSS method. The analysis resulted that the critical satisfaction factors to customer satisfaction are empathy, tangibility, and reliability; also, customer satisfaction will be directly resulted in repurchase intention of customer.